Analgesic and Anti-Inflammatory Activities of Sophocarpine from Sophora viciifolia Hance - F. L. Wang (Hindawi Limited, 2021)
Sophora viciifolia Hance is an edible plant used in traditional Chinese medicine. Sophocarpine, a tetracyclic quinolizidine alkaloid, is one of the most abundant active ingredients in Sophora viciifolia Hance. Here, we study the analgesic and anti-inflammatory effects, as well as the acute toxicity of sophocarpine from Sophora viciifolia Hance in mice. Sophocarpine (20, 40, and 80 mg/kgbw) significantly prolonged the delay period before a hot plate reaction occurred (all P<0.05), and the delay before a tail-flick response was induced by a warm bath (P<0.05; P<0.01). Sophocarpine (40, 80 mg/kg) resulted in dose-dependent inhibition of the writhing reaction induced by acetic acid in mice (P<0.05; P<0.001, respectively). Sophocarpine (80 mg/kg) reduced the total duration of a formalin-induced pain response (P<0.05). Sophocarpine prolonged the foot-licking latency of mice after the hot plate reaction, and this effect was antagonized by calcium chloride and enhanced by verapamil. Sophocarpine (20, 40, and 80 mg/kg) significantly inhibited xylene-induced ear edema (P<0.01; P<0.001; P<0.001, respectively) and the penetration of acetic acid-induced dye into the peritoneal cavity (P<0.01; P<0.01; P<0.001, respectively). It also reduced the levels of proinflammatory cytokine interleukin (IL)-1β, IL-6, and prostaglandin E2 (P<0.05, P<0.01, P<0.001) and those of serum nitric oxide (P<0.05). The results of this study suggest that sophocarpine possesses certain analgesic and anti-inflammatory activities, which may be related to calcium and inhibition of the secretion of inflammatory factors.